A capacity analysis framework for multi-hazard early warning in coastal communities. (2018) - Haigh, Richard; Amaratunga, Dilanthi; Hemachandra, Kinkini
Abstract: Coastal regions are an important focus of development, are densely populated and are typically exposed to a range of hazards. A critical aspect of disaster risk reduction (DRR) is the efficient functioning of multi-hazard early warning systems (MHEWS) that are owned by States but require a high degree of international and multilateral cooperation. They are designed according to well-defined operational standards which must be uniformly implemented across the broad range of activities and projects. However, progress in early warning (EW) is uneven across Asia, in terms of high-risk and hazard type resulting low-capacity countries falling behind. The Intergovernmental Coordination Group (ICG) of Indian Ocean Tsunami Warning and Mitigation System (IOTWMS) has a mandate to enhance awareness and implementation by Member States of the procedures for risk assessment and effective functioning of the "last mile" of the MHEWS within communities. This mandate corresponds to priority aims identified in the Sendai Framework of 2015 on DRR. The ICG has identified the considerable demand amongst Indian Ocean Member States for capacity building that will enhance this foundation of procedural knowledge and promote its take-up on a sustained and sustainable basis, as a step towards the implementation of these DRR aims. This paper describes the results of the first stage of a longer-term study into the capacity of MHEW across Asia. The study is being carried out by fifteen Higher Education Institutes (HEIs) across Europe and Asia, along with several socio-economic actors in the region. The initial study will focus on five countries that include communities highly exposed and vulnerable to the threat posed by multiple coastal hazards: Indonesia; Maldives; Myanmar; Philippines; and Sri Lanka. The first phase of the study involved the development of a regional capacity analysis framework for MHEW. The framework covers a range of dimensions, such as legislative, planning, infrastructure, technical and scientific, and institutional partnerships. The framework was developed through the processes of consultation and needs assessments by the project partners and relevant socio-economic actors. The resultant framework will be used as the basis for detailed capacity analysis studies in the five target countries, as well as a wider regional perspective. The analysis findings will underpin later capacity building activities across the region.